Technological breakthroughs in modern wireless sensor applications - Sharif, Hamid R. 1958-; Kavian, Yousef S., 1978- (Information Science Reference, an imprint of IGI Global, 2015)
"This book brings together new ways to process and monitor data, and to put it to work in everything from intelligent transportation systems to healthcare to multimedia applications"-- Provided by publisher
"Premier reference source"--Cover
Keywords: Wireless sensor networks.; Wireless communication systems.; elektronické knihy; electronic books